Edukasi terkait langkah pengembangan formula dan registrasi kosmetik melalui webinar - Sucilawaty Ridwan; Wahida Hajrin; Windah Anugrah Subaidah; Eskarani Tri Pratiwi (INDRA: Jurnal Pengabdian kepada Masyarakat, 2023)
Indonesia is a potential market for cosmetics. Students and lecturers at Departments of Pharmacy developed various cosmetic formulas, but limited to research or publications only. Lack of knowledge about the stages of developing good cosmetic formulas, good manufacturing cosmetics, and the steps in registration of cosmetic preparations is the main cause in developing cosmetic products. The method used in this community service is online conference. The participants were given a pretest and posttest to determine their level of understanding about cosmetics formula development and registration. About 190 participants attended the conference. Assessment by pretest and posttest obtained an average result of 50.22 ± 13.36 and 70.05 ± 18.97 respectively. The results show that there is a significant difference between pretest and posttest. The conference was considered good by the participants with an average score of 3.68 of 4. This conference provided increased knowledge to participants regarding the development of cosmetic formulas and the steps in cosmetic registration.